Gender violence in higher education: predictors factor analysis - Ferrer Pérez, Victoria A.; Bosch Fiol, Esperanza; Navarro Guzmán, Capilla (Anales de Psicología / Annals of Psychology, 2011)
The consideration of violence against women as a social problem and its inclusion on political agenda in Spain has taken a great force in ultimate years. Among the actions that are indicated like important in this context is to include this subject in college education of future professionals that should confront it. In the framework of a large investigation, we analyze prediction factors that differentiate between university students that has studied subjects with domestic violence contents of them has not in a sample of 1395 university students. We administered them an ad hoc interview and the "Inventario de Pensamientos Distorsionados sobre la Mujer y la Violencia". The results show that among prediction variables of this circumstance there is so much socio demographic variables, as of prior edu-cation, perception of the frequency and causes of the problem and beliefs around him. Likewise, these results show that the variables that better predict to have studied this type of matters they differ between men and women. The implications of these results are analyzed.